Diffraction post-processing of 3D dislocation dynamics simulations for direct comparison with micro-beam Laue experiments - Hofmann, F; Keegan, S; Korsunsky, A (2012)
We present a method of computing lattice rotations and elastic strains due to 3D dislocation structures discretised into straight segments. Combined with ray-tracing, it enables virtual scattering experiments where X-ray diffraction patterns that would arise from such dislocation structures are simulated. We demonstrate the diffraction post-processing of a Frank-Read source simulated using the ParaDiS discrete dislocation dynamics code. This simulation is compared to experimental synchrotron X-ray micro-beam Laue diffraction measurements of a single grain within a deformed nickel polycrystal. The simulated pattern captures the experimentally observed anisotropic broadening of Laue reflections and illustrates that heterogeneous and anisotropic lattice (re)orientation effects dominate the peak shape. © 2012 Elsevier B.V.